Simulation studies and experimental measurement of the air bearing slider - Ho, Jefferson Rui Ming. (2011)
The ever-increasing demand of high areal density in hard disk drives has led to a continuous reduction in the magnetic spacing between the head and the media. This magnetic spacing can be decreased by reducing the roughness of the head and disk surfaces, thickness of the disk lubricant and the mechanical spacing between the flying head and the disk. The mechanical spacing or flying height, in particular, has been greatly reduced to the nanometer regions. At such ultra-low flying height, slider-disk contact becomes unavoidable due to the flying height variations of the sliders, surface waviness of the disk and short range forces in the head-disk interface.